Severe plastic deformation by equal channel angular pressing: product quality and operational details - Anibal de Andrade Mendes Filho; Erika Fernanda Prados; Gustavo Trindade Valio; José Benaque Rubert; Vitor Luiz Sordi; Maurizio Ferrante (Materials Research, 2011)
As a technique, Equal Channel Angular Pressing (ECAP) is simple and inexpensive. However, if die manufacture and operational details are not carefully planned and implemented, difficulties arise, which can interfere with the product characteristics and the pressing operation itself. The present paper offers guidelines on die design and manufacture, emphasizing geometry, material and heat treatment. Further, operational parameters such as lubrication, pressing temperature, deformation routes, die closure procedure and the influence of channel cross section on maximum acceptable load are described. Additionally, the effects of those variables on the product characteristics (deformation level and homogeneity) and integrity, plus process control and safety, are discussed.